The Copyright Amendment (Access Reform) Bill 2021 And Open Access: A Comparative Legal Perspective - Koutras, Nikos (Thomson Reuters (Sweet and Maxwell), 2023)
Open access (OA) is critical for improving people’s knowledge backgrounds. Furthermore, it hasthe potential to enable global change by improving the accessibility of study findings. As far as the purpose of knowledge circulation is concerned, accessto sources of information is of crucial importance. In recent times, digitalisation has ameliorated such access. The ongoing digitalisation undermines the copyright law regime. In this approach, statutory interpretation may serve as a “vessel” through which legal arguments for protection might be provided. However, the common law viewpoint appears to be limited. As a result, the law must effectively address the complex problem of copyright protection. The paper is composed of three parts. The first part examines the concept of multilevel governance and its confluence with European copyright legislation. The second section analyses the operationalisation of open access practice by drawing on European examples (i.e., the European Universities Association and the Taverne amendment of the Dutch Copyright Act). The final part focuses on the state of open access implementation in Australia, using data from the Curtin Open Knowledge Initiative (COKI) and comparing it to data from the Netherlands case.1 Australian stakeholders’ (e.g., universities, public institutions, individuals, etc.) participation in the public inquiry on draft copyright reform legislation (i.e., submissions on an exposure draft of the Copyright Amendment (Access Reforms) Bill 2021) enriches the discussion. The article contends that the public investigation into the Copyright Amendment (Access Reform) Bill 2021 is characterised by multilevel governance. The article contends that multilevel governance dynamics can improve applicable copyright policy and establish an informed regulatory framework for copyright protection. The paper concludes by presenting four recommendations for the Copyright Act 1968 (Cth), which could supplement the current legal system for protection.